Global Solutions of Certain Second-Order Differential Equations with a High Degree of Apparent Singularity - Sasaki, R.; Takemura, K. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
Infinitely many explicit solutions of certain second-order differential equations with an apparent singularity of characteristic exponent −2 are constructed by adjusting the parameter of the multi-indexed Laguerre polynomials.